A new species of Eupholus Boisduval, 1835 from Indonesian New Guinea with notes on the taxonomy of the genus (Coleoptera, Curculionidae) - Bollino, Maurizio; Anderson, Robert S. (Zootaxa, 2024)
Eupholus sulisi Bollino and Anderson sp. nov. is here described from the Indonesian portion of New Guinea, and separated from the most similar species E. prasinus Heller 1910 and E. humeralis Heller 1908. The structure of the everted endophallus examined in 38 of 71 species of Eupholus Boisduval 1835 supports the recognition of three groups within the genus, the Eupholus loriae-group, Eupholus schoenherri-group, Eupholus alternans-group, and Eupholus antonkozlovi Porion and Audibert, which does not fall into the three aforementioned groups.